Implementation of Land Dispute Resolution with Justice - Hulu, Fonaha; Ambarita, Lenny Mutiara; Damanik, Pandapotan; Gulo, Yurulina (UNISSULA, 2023)
The purpose, as with various other arrangements, is to ensure legal certainty, provide legal protection for the people in the context of supporting sustainable development without ignoring the principle of environmental sustainability. The purpose of this research is to analyze the application of equitable land dispute resolution because so far the regulation of land dispute resolution has not been equitable, giving rise to various disputes in the process of resolving land cases. The research method used in this research is the normative juridical method. In addition, it is necessary to establish a special court that handles land issues, namely the Agrarian Court, a special court for land dispute resolution under the Supreme Court of the Republic of Indonesia. Novelty in this research with the establishment of institutions and laws and regulations that specifically deal with the issue of fair land dispute resolution is expected that the Agrarian Court can fulfill a sense of justice for the parties in the settlement of land disputes that have occurred so far in the community.